The efficacy and safety of micropulse transscleral laser treatment in glaucoma: a systematic review and meta-analysis - Qiying Ling; Ziyan Cai; Xinyue Zhang; Xuanchu Duan (BMC Ophthalmology, 2023)
Abstract Objective Micropulse transscleral laser treatment (mTLT) is the latest alternative intraocular pressure (IOP) lowering approach for glaucoma patients. This meta-analysis aims to evaluate the efficacy and safety of mTLT and continuous wave transscleral cyclophotocoagulation (CW-TSCPC) for the treatment of glaucoma. Methods We searched the PubMed, Embase, and Cochrane Library of Systematic Reviews databases from January 2000 to July 2022 to identify studies that, evaluated the efficacy and safety of mTLT in glaucoma. There were no restrictions regarding study type, patient age, or type of glaucoma. We analysed the reduction in IOP and the number of anti-glaucoma medications (NOAM), retreatment rates, and complications between mTLT and CW-TSCPC treatment. Publication bias was conducted for evaluating bias. This systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA 2020) reporting guideline. Results We identified 6 eligible studies of which only 2 RCTs and 386 participants with various types of glaucoma at different stages were ultimately included. The results revealed significant IOP decreases after mTLT up to 12 months and significant NOAM reductions at 1 month (WMD=-0.30, 95% CI -0.54 to 0.06), and 3 months (WMD=-0.39, 95% CI -0.64 to 0.14) in mTLT compared to CW-TSCPC. Moreover, the retreatment rates (Log OR=-1.00, 95% CI -1.71 to -0.28), hypotony (Log OR=-1.21, 95% CI -2.26 to -0.16), prolonged inflammation or uveitis (Log OR=-1.63, 95% CI -2.85 to -0.41), and worsening of visual acuity (Log OR=-1.13, 95% CI -2.19 to 0.06) occurred less frequently after mTLT. Conclusion Our results demonstrated that mTLT could lower the IOP until 12 months after treatment. mTLT seems to have a lower risk of retreatment after the first procedure, and mTLT is superior to CW-TSCPC with respect to safety. Studies with longer follow-up durations and larger sample sizes are necessary in the future. Trial registration number INPLASY202290120.